Obstructive Sleep Apnea with Paradoxical Vocal Cord Movement in Children during Sleep Endoscopy: Case Series - Maxwell Newby; Sarah Callaham; Michele Carr (Hindawi Limited, 2020)
Objective. To describe a series of pediatric cases of obstructive sleep apnea (OSA) with paradoxical vocal cord movement noted on drug-induced sleep endoscopy (DISE). Materials and Methods. Case series and chart review of children who had undergone DISE for OSA that showed PVCM. Results. Three cases where paradoxical vocal cord motion (PVCM) was noted during DISE are described. Two had an enlarged adenoid, and one had no other site of obstruction. Two were treated with adenoidectomy and antireflux medications. One received proton pump inhibitors alone. In all 3 cases, OSA symptoms resolved. Conclusion. This case series of documented obstructive sleep apnea related to paradoxical vocal cord movement suggests that this entity occurs during sleep with airway obstruction. Further clarification of etiology of PVCM during OSA and its management is needed.